PENGARUH TINGKAT LITERASI KEUANGAN PEMILIK USAHA TERHADAP PENGELOAAN KEUANGAN. STUDI KASUS : UMKM DEPOK - Birawani D. Anggraeni (Program Pendidikan Vokasi Universitas Indonesia, 2016)
Financial literacy affects a person's way of thinking on the financial condition and influence strategic decisions interms of finances and better management for business owners.This study uses secondary data as study materials which will be given to the micro level that businesses with aturnover of up to 300M per year in which the segment in general do not have good financial records to then beused as financial statements. In a study using 12 samples of SMEs in the area of Depok randomly selected. Thisstudy uses processed using descriptive statistics as well as the weighting at the level of financial literacy.Results from this study indicate that the level of financial literacy of low business owners so that the effect on theability to manage finances. This is reflected in the financial results of the attitude of business owners where theymerely record the receipt and expenditure of financial business without being accompanied by supporting documentsstorage. Business owners so far have not made the budget as a basis for evaluating the performance of theirbusinesses. In addition the ability of business owners to manage cash surplus and deficit shows the majority of usingbanks or non-banks. They have not yet reached the stage of investing in financial products.Simple research is expected to contribute to the field of accounting related to business continuity, especially in termsof financial management business through increased financial literacy.Keywords: financial literacy, financial management, record keeping, budget.